1970
DOI: 10.3758/bf03335792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of checkerboard pattern stimulation on evoked cortical responses in relation to check size and visual field

Abstract: Cortical evoked responses to checker board stimulation were studied as a function of check size and visual field. Stimuli were presented to the upper, central, and lower parts of the retina. Regardless of check size, largest potentials were obtained to lower-field stimulation; central-field stimulation yielded intermediate responses; upper-field stimulation produced the smallest responses. Maximal responses were obtained to intermediate check sizes during lower-field stimulation and to the smallest checks duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1971
1971
1983
1983

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The known nasal-temporal, retino-cortical conduction time difference of 3-5 msec (15) is of the right magnitude to provide an explanation with the post hoc assumption that: stimula•tion directed toward the fovea from the lower visual field is preeminent in the resultant cortical integration. (Research supports this particular combination though the converse would do as well since all combinations of stimulus conditions were used (16,17). Given this assumption, the positive relative depth with equal luminance to both eyes and infinite exposure is directly derived as is the observed symmetry of the "control" data about point P. The positive and negative displacement of the simultaneous neutral point with equal exposure durations ( Figures 6 and 7) is explained as an additive interaction of the depth induced by the nasaltemporal delay with the characteristic, opposed depth displacements of the post hoc categories.…”
Section: Discussionmentioning
confidence: 99%
“…The known nasal-temporal, retino-cortical conduction time difference of 3-5 msec (15) is of the right magnitude to provide an explanation with the post hoc assumption that: stimula•tion directed toward the fovea from the lower visual field is preeminent in the resultant cortical integration. (Research supports this particular combination though the converse would do as well since all combinations of stimulus conditions were used (16,17). Given this assumption, the positive relative depth with equal luminance to both eyes and infinite exposure is directly derived as is the observed symmetry of the "control" data about point P. The positive and negative displacement of the simultaneous neutral point with equal exposure durations ( Figures 6 and 7) is explained as an additive interaction of the depth induced by the nasaltemporal delay with the characteristic, opposed depth displacements of the post hoc categories.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to suggestions by White (1969) .N: that VEP amplitude differences may be used as a basis for testing vision, especially refractive errors in persons who cannot verbalize well enough for adequate testing by many of the currently used testing methods (e.g., retarded individuals or young children). Eason et al (1970) stimulated the upper and lower halves of the visual field and reported that VEP amplitude varied with visual field and check size. That is, checks subtending 10' of angle produced larger VEPs in the upper field, while checks subtending 40' of visual angle were optimal for lower field stimulation.…”
Section: Introductionmentioning
confidence: 99%